A quantum blockchain-enabled framework for secure private electronic medical records in Internet of Medical Things - Qu, Zhiguo; Zhang, Zhexi; Zheng, Min (Information sciences, 2022)
•Novel quantum blockchain with proprietary data structure and its implementation.•The block hash value stored as one qubit with parallel computing capability.•Quantum electronic medical records guarantee data security and privacy by resisting quantum attacks. There is a rising need for healthcare as a result of rising public awareness of health issues. Electronic medical records include extremely confidential and sensitive information, and blockchain technology can enable the safe exchange of these records across various medical organizations. The current blockchain system is susceptible to quantum computer attacks, nevertheless, as a result of the advent of quantum computers. This research designs a novel distributed quantum electronic medical record system and suggests a new private quantum blockchain network based on security considerations. The blocks in this quantum blockchain’s data structure are linked via entangled states. The time stamp is automatically formed by connecting quantum blocks with controlled activities, which lowers the amount of storage space needed. Each block’s hash value is recorded using just one qubit. The quantum information processing is detailed in depth in the quantum electronic medical record protocol. Every medical record can be tracked, and the security and privacy of electronic medical records in Internet of Medical Things systems can be guaranteed. The protocol also ditches the traditional encryption and digital signature algorithms in favor of a quantum authentication system. According to the mathematical analysis, the quantum blockchain network has strong security against attacks from quantum computers since it can withstand External attack, Intercept-Measure-Repeat attack and Entanglement-Measure attack. The quantum circuit diagram for deriving the hash value is provided, along with the correctness and traceability analysis of the quantum block. The comparison between the proposed quantum blockchain model and a few other quantum blockchain models is also included.